Treatment Of ACNE Vulgaris With New Polyherbal Formulations - Sachidananda Y N; Ananad Kumar B H (Wolters Kluwer Medknow Publications, 2001)
One hundred and five patients with active lesions of acne vulgaris were included in the open clinical trial. All the patients were administered tablets containing multiple herbal drugs (purim), at a dose of 2 tablets twice daily for four weeks. Simultaneously, they were instructed to apply A herbal cream (Clarina) twice daily on the affected area of acne lesion twice daily for four weeks. The response to treatment was excellent in mild to moderate acne (Grade I & II) after 4 weeks of treatment. In severe acne with large papules and pustules, the response was also significantly good, in healing the papules and pustules. There were no local or systemic side effects seen in all these patients. Thus, this polyherbal cream (Clarina) along with a polyherbal tablet (Purim) tablets was useful in treating patients with various degrees of acne.